Understanding equanimity from a psychological perspective: implications for holistic well-being during a global pandemic. Issue 9 (21st October 2021) - Jijina, Parisha; Biswas, Urmi Nanda
ABSTRACT: The cultivation of equanimity has been emphasized in various indigenous philosophies and contemplative practices. This paper aims to develop an expansive understanding of equanimity as a distinct psychological construct. Thirty experts from various traditions such as Buddhism, Vedic studies, meditation, and yoga were interviewed on their understanding and insights into equanimity. The findings suggest equanimity as an even-mindedness towards the varied hedonic and affective experiences. The cognitive, affective, and conative mechanisms of equanimity such as increased distress tolerance, hedonic neutrality, and reduced reactivity are outlined. At the interpersonal level, equanimity entails impartiality and reduced bias towards others. The challenges one may face during the cultivation of equanimity have been suggested by the experts. The implications of cultivating equanimity have been examined in the context of adaptive coping and holistic wellbeing in the current pandemic situation, dealing with compassion fatigue, and the development of indigenous leadership practices.